The wake of the unseen object - Kizzia, Tom, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2020)
When The Wake of the Unseen Object was published in 1991, I imagined it might reach readers as a work of "literary travel," a genre then filling the shelves at the front of bookstores. The understated arc of the book, after all, was the education of a traveler: his progress, from early awkward door-to-door questioning to a deeper understanding and sense of place. His lessons in paying attention and seeing the world as it is, unburdened by romanticism or its inverse, disillusion. His struggles to free himself from that peculiar little character who shows up briefly in Chapter Two, "the God of Things as They Ought to Be." This new edition of the book reproduces the text as it originally appeared, without corrections or updates. Terms such as "Eskimo" and "Indian," now subject to reconsideration but common and accepted in that day, remain in place, along with then-standard applications of the words "Inupiat" and "Inupiaq," as noun and adjective.--Provided by publisher.
Introduction to the new edition -- 1. Forest Primeval -- 2. Spirit World -- 3. People of Kauwerak -- 4. Return of the Native -- 5. Indian Country -- 6. Animal Powers -- 7. Red Devil -- 8. Icons -- 9. River People -- 10. Yupiit Nation -- 11. The Wake of the Unseen Object.
New edition. Originally published in 1991.
Keywords: Eskimos -- Alaska -- Social life and customs; Indians of North America -- Alaska -- Social life and customs; Alaska -- Description and travel